Pengaruh Store Atmosphere, Kualitas Produk, dan Perilaku Konsumen Terhadap Keputusan Pembelian - Damayanti, Kadek Mita; Susanti, Putu Herny; Putri Agustina, Made Dian (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to partially and simultaneously influence store atmosphere, product quality, and consumer behavior on purchasing decisions at Viory distributions in Panjer, Denpasar. The population in this study was all consumers of the Viory distribution in Panjer, Denpasar. The number of samples used is 100 people taken using purposive sampling method. Data analysis using multiple linear regression analysis. The results of the analysis show that the store atmosphere variable has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions, consumer behavior has a positive and significant effect on purchasing decisions, as well as store atmosphere, product quality, and consumer behavior simultaneously have a positive and significant effect on purchasing decisions.